APPLICATION OF THE ASSURE LEARNING MODEL ON GEOMETRY - Patma Sopamena; Ayani Lifumangau; Syafruddin Kaliky; Fahruh Juhaevah; Nurlaila Sehuwaky; Nurlaila Sopamena (MATEMATIKA DAN PEMBELAJARAN, 2021)
This study aims to describe the activities carried out by students and teachers in the learning process and improving student learning outcomes after the learning process through the ASSURE model. This research classifies as a classroom action research with a mixed-method approach, namely, descriptive qualitative and quantitative approaches. The research subjects were 30 students of class VII-5 MTs Negeri Ambon with two learning cycles. The results showed that student learning activities before the cycle action had not been seen, such as not paying attention to the teacher's explanation, embarrassed to ask or answer, and the work results to solve the questions given still relying on the answers of their friends. After the cycle action showed an increase in student activity, among others, students focused more on listening to the teacher's explanation, began to dare to ask questions, opinions, or answers, and began to be confident in their work. Also, there was an increase in student test results. Before the action of the pre-test results, the mean score of the students was 25.90. After the action, the students 'average score in the first cycle was 62.07, and in the second cycle, the students' average score was 89.99.